2022
DOI: 10.3390/molecules27061935
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analytical Study on Chemical Transformations and Detoxification of Model Phenolic Pollutants during Various Advanced Oxidation Treatment Processes

Abstract: Advanced oxidation processes (AOPs) have been introduced to deal with different types of water pollution. They cause effective chemical destruction of pollutants, yet leading to a mixture of transformation by-products, rather than complete mineralization. Therefore, the aim of our study was to understand complex degradation processes induced by different AOPs from chemical and ecotoxicological point of view. Phenol, 2,4-dichlorophenol, and pentachlorophenol were used as model pollutants since they are still co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Effect of diluted samples at final t TR (see Table I) was evaluated on water flea D. magna according to procedure described in literature. 24,25 Incubation of organisms for 48 h led to impact on their mobility that was quantified as inhibition (Table II, INH). The higher INH, the higher the negative effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of diluted samples at final t TR (see Table I) was evaluated on water flea D. magna according to procedure described in literature. 24,25 Incubation of organisms for 48 h led to impact on their mobility that was quantified as inhibition (Table II, INH). The higher INH, the higher the negative effect.…”
Section: Resultsmentioning
confidence: 99%
“…Instrumental analyses.-The concentration of phenol in model samples during treatment was determined by standard spectrophotometric method with 4-aminoantipyrine (phenol index) 23 and by HPLC-DAD using the method described in Kravos et al 24 Degradation products were identified and quantified by several methods: HPLC-DAD, LC-MS, solid-phase microextraction (SPME) or liquid-liquid extraction (LLE) followed by GC-MS, and ion chromatography (IC); optimized methods are described in Kravos et al 24 The following chemicals were used for quantification of by-products with HPLC-DAD: hydroquinone (HDQ; Fluka, ⩾99%), catechol (CAT; Fluka, ⩾99%), 2,4-dichlorophenol (DCP; Sigma Aldrich, 98%); for quantification with IC: disodium fumarate (FM; Fluka, 99%), oxalic acid (OX; Fluka, ⩾99%). Other byproducts (i.e., succinic, maleic, formic, propionic acid; chlorohydrocarbons, chlorophenols, and p-benzoquinone) were semiquantified or only identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenol and chlorophenols (CPs) are representative examples of a wider group of phenolic pollutants. Their presence in the environment is due to intensive historical use, drinking water chlorination, biodegradation of organochlorinated chemicals, and their importance in the chemical industry [59].…”
Section: Pesticide Use In the Worldmentioning
confidence: 99%
“…PCP was detected in 760 seafood samples collected from coastal cities in Zhejiang Province, and 11 species of seafood were detected to varying degrees, indicating that the main source of PCP contamination in coastal Zhejiang Province is the large-scale illegal use of PCP in coastal mudflats and ponds during seawater fish farming for the purpose of killing snails and other marine organisms to clear the ponds. PCP in the surface soil of mudflats and ponds is easily combined with minerals and organic matter in the soil, thus fixing PCP contaminants in the sediment for a long time [35,36]. When shellfish, crabs, and shrimps are grown in the sediment in mudflats and ponds, PCP is absorbed and transported into the sediment, thus affecting human health and safety.…”
Section: Sample Analysismentioning
confidence: 99%